Explicație pas cu pas:
a) 7x - 7 = 6 - 3x - 3
7x +3x = 3+7
10x =10
x= 10/10
x =1
C) x^2 + x= x² + 2x + 1
x-2x =1
-x =1
x = - 1
e) 5 – 10x + 1 = 4x + 12+ 8
-10x +6 = 4x +20
-10x - 4x = 20 - 6
-14x = 14
x = - 14/14
x = - 1
b) 3x – 4 = x + 2(x - 2)
3x - 4 = x + 2x - 4
3x - 4 = 3x - 4
3x - 3x = - 4+4
0=0
x aparține lui R
d) 2(2x - 5) = 4(x - 2) - 6
4x - 10 = 4x - 8-6
4x - 4x = - 14 +10
0 = - 4
x aparține mulțimii vide
f) -102-2-2[(-4)5:44 - 2]} = -2x
-104 - (-20: 44 - 2) = - 2x
Aici lipsește o acolada